Screening Candidate Effectors of the Bean Bug Riptortus pedestris by Proteomic and Transcriptomic Analyses - Fu, Weichuan; Liu, Xingzhou; Rao, Cong; Ji, Rui; Bing, Xiaoli; Li, Jinbu; Wang, Yueying; Xu, Hao (Frontiers in Ecology and Evolution, 2021)
The damage of Riptortus pedestris is exceptional by leading soybean plants to keep green in late autumn. Identification of the salivary proteins is essential to understand how the pest-plant interaction occurs. Here, we have tried to identify them by a combination of proteomic and transcriptomic analyses. The transcriptomes of salivary glands from R. pedestris males, females and nymphs showed about 28,000 unigenes, in which about 40 % had open reading frames (ORFs). The predicted proteins in the transcriptomes with secretion signals were obtained. Many of the top 1,000 expressed transcripts were involved in protein biosynthesis and transport, suggesting that the salivary glands produce a rich repertoire of proteins. In addition, saliva of R. pedestris males, females and nymphs was collected and proteins inside were identified. In total, 155, 20 and 11 proteins were, respectively, found in their saliva. We have tested the tissue-specific expression of 70 genes that are likely to be effectors, either because they are homologs of reported effectors of other sap-feeding arthropods, or because they are within the top 1,000 expressed genes or found in the salivary proteomes. Their potential functions in regulating plant defenses were discussed. The datasets reported here represent the first step in identifying effectors of R. pedestris.